Cognitive Representation of Treatment-Related Symptoms in Older Adults With Cancer. Issue 3 (May 2017) - Loerzel, Victoria
Abstract : Background: Adults, 65 years or older, are the most common age group diagnosed with cancer. However, little is known about their beliefs (representations) regarding treatment-related symptoms or how they make decisions to manage those symptoms at home. Objective: The aim of this study is to explore symptom representation of treatment-related symptoms in older adults with cancer. Methods: A total of 100 older adults in treatment for cancer completed a standardized measure of symptom representation. Demographic and other patient variables were also collected. Analysis of variance, t tests, and Pearson correlations were used for analysis. Results: Fatigue was both the most common and most noted symptom; however, several most noted symptoms were not common. Overall, older adults believed symptoms were caused by either their cancer or treatment and were unsure if symptoms would last a long time. They were able to recognize symptom consequences but were unsure about their ability to control symptoms. Adults who reported more comorbid illnesses and a higher number of symptoms believed that treatment-related symptoms had higher consequences. Conclusions: Findings suggest that older adults experience symptom-related consequences but question the impact that their actions will have on symptom severity. This may contribute to older adult's lack of active symptom self-management. Implications for Practice: Patient education strategies need to address these representations and new interventions may need to be developed to reinforce symptom consequences and empower older adults to self-manage symptoms.